Фінансова модель системи управління динамічною стійкістю холдингу - Лазарева, М.Г. (Економіка промисловості, 2014)
Розглянуто використання в практиці українських інтергрованих об’єднань вартістного підходу. Запропоновано фінансову модель системи управління динамічною стійкістю холдингу, яка складається з двох моделей: вільних грошових потоків для оцінювання існуючого бізнез-портфеля і поточного управління вартістю щодо новопридбаних компаній (авторська розробка). Рассмотрено использование в практике украинских интегрированных объединений стоимостного подхода. Предложена финансовая модель системы управления динамической устойчивостью холдинга, которая состоит из двух моделей: свободных денежных потоков для оценивания имеющегося бизнес-портфеля и текущего управления стоимостью для вновь приобретенных компаний (авторская разработка). The main strategic goal of the firm in modern conditions is the growth of business value that is the target function at the dynamic stability system of holding companies. For getting the best results it is needed to have the adequate tools that allow measuring the value with the high level of reliability, modern concepts, and models. The main goal of the research is the creation of such a kind of financial models that allows measuring the value of the business including the current business portfolio, ventures business, and just bought businesses. The strategic task of holding company in the dynamic stability system is the effective management of integrated balanced business portfolio,the stable competitive position of businesses at the markets, which allows getting the growth of value of every businesses of business portfolio. Positive effect of synergy is achieved for account of: centralized strategic management; using the unified corporate standards; savings of transactions costs; operational economic independence of businesses (the most preferable management model for diversified holding companies).Financial model must have the capacity for measuring the value of business portfolio existed including just bought businesses that are at the incubation period and have not passed the adaptive period in holding company. Besides that it must allow evaluating the new businesses that will be included into business portfolio. The most suitable model for realization of these objectives (except businesses that are at the incubation period) is the Free Cash Flow Model. It is reasonable to use this Model as the basic model for evaluation because it is more adaptive to the conditions of Ukraine than conventionally used VBM indicators, such as, for example, EVA.The model has limited usage for the valuation of assets of the business portfolio that does not bring the value at present (including just purchased businesses) but perhaps will generate cash flows in the future. For this purpose the Model of Current Value (CV-Model) is suggested. The basic premises of the model proposed are as follows: despite the negative results in prior periods, when increasing revenues, profits and assets, the value increases (reducing losses). The model uses the profitability index of sales and index of assets. Suggested financial model of the dynamic stability system of holding companies consists of two basic components: FCF (Free Cash- Flow) Model and CV-Model (Current Value). It allows measuring the value of exist business portfolio of holding companies aside from the stage of development of individual business and gives the results with the sufficient reliability.